MENCIPTAKAN KEPUASAN TOTAL PELANGGAN MELALUI PENGGUNAAN QUALITY FUNCTION DEPLOYMENT PADA AGRIBISNIS SAYURAN [Creating Total Customer Satisfaction by Using Quality Function Deployment in Vegetables Agribusiness] - . Abidin; . Marimin (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2001)
In the product design and development processes, Quality Function Deployment (QFD) provides a comprehensive, systematic approach to ensure that the products meet or exceed customer expectations. This paper reports the results of vegetables customers survey in Jakarta. Analytical Hierarchy Process (AHP) method was used for weighing the result of survey, and the customer expectation were translated using QFD. To meet the biggest customer expectation, i.e. vegetables freshness, Just In Time (JIT) concept was utilized.